2007
DOI: 10.1071/rd06063
|View full text |Cite
|
Sign up to set email alerts
|

Effects of levonorgestrel on ovulation and oestrous behaviour in the female tammar wallaby

Abstract: Subcutaneous hormone implants are a useful method for managing overabundant marsupials in restricted enclosures in Australia. Levonorgestrel induces long-term infertility in the kangaroo, tammar wallaby and koala, although the contraceptive mechanism of levonorgestrel is unknown for any marsupial. In the present study, it was investigated if insertion of a single levonorgestrel or control implant at the time of reactivation of the diapausing blastocyst affected the subsequent post-partum oestrus or the precedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 31 publications
0
9
2
Order By: Relevance
“…Whilst here we have not determined if LNG treatment blocked ovulation in the koala, it certainly blocked oestrous behaviour in this induced ovulatory species. Interestingly, our results in 6-12 koalas and that of Crawford et al (2011) in the possum, appear to be in contrast to those previously reported by Hynes et al (2007) for the tammar wallaby, where by follicular activity continued unabated during progestogen treatment. This difference between species is not surprising given follicular growth in the tammar wallaby occurs during a period of elevated progesterone in the final third of pregnancy (Tyndale-Biscoe and Renfree, 1987).…”
Section: -11contrasting
confidence: 57%
See 4 more Smart Citations
“…Whilst here we have not determined if LNG treatment blocked ovulation in the koala, it certainly blocked oestrous behaviour in this induced ovulatory species. Interestingly, our results in 6-12 koalas and that of Crawford et al (2011) in the possum, appear to be in contrast to those previously reported by Hynes et al (2007) for the tammar wallaby, where by follicular activity continued unabated during progestogen treatment. This difference between species is not surprising given follicular growth in the tammar wallaby occurs during a period of elevated progesterone in the final third of pregnancy (Tyndale-Biscoe and Renfree, 1987).…”
Section: -11contrasting
confidence: 57%
“…These observations suggests that LNG suppressed oestradiol secretion from the existing dominant Graafian follicle (at oestrus) and also subsequently prevented development of the dominant follicle of the next cycle. These results are consistent with progestogen studies in eutherian species, but somewhat contrary to what has been observed in the tammar wallaby (Hynes et al, 2007).…”
Section: -11contrasting
confidence: 33%
See 3 more Smart Citations